CCR7/dendritic cell axis mediates early bacterial dissemination in Orientia tsutsugamushi-infected mice - Liang, Yuejin; Wang, Hui; Gonzales, Casey; Thiriot, Joseph; Sunyakumthorn, Piyanate; Melby, Peter C.; Sun, Jiaren; Soong, Lynn (Frontiers in Immunology, 2022)
Scrub typhus is a life-threatening zoonosis caused by the obligate intracellular bacterium Orientia tsutsugamushi (Ot) that is transmitted by the infected larvae of trombiculid mites. However, the mechanism by which Ot disseminates from the bite site to visceral organs remains unclear; host innate immunity against bacterial dissemination and replication during early infection is poorly understood. In this study, by using an intradermal infection mouse model and fluorescent probe-labeled Ot, we assessed the dynamic pattern of innate immune cell responses at the inoculation site. We found that neutrophils were the first responders to Ot infection and migrated into the skin for bacterial uptake. Ot infection greatly induced neutrophil activation, and Ot-neutrophil interaction remarkably promoted cell death both in vitro and in vivo. Depletion of neutrophils did not alter bacterial dissemination in mice, as evidenced by similar bacterial burdens in the skin and draining lymph nodes (dLN) at day 3, as well as in the lungs and brains at day 14, as compared to the control mice. Instead, dendritic cells (DCs) and macrophages played a role as a Trojan horse and transmitted Ot from the skin into dLN. Importantly, the absence of homing receptor CCR7 or neutralization of its ligand, CCL21, significantly impaired DC migration, resulting in reduced bacterial burdens in dLN. Taken together, our study sheds light on a CCR7/dendritic cell-mediated mechanism of early Ot dissemination and provides new insights into therapeutic and vaccine development strategies for scrub typhus.